EXAMINING THE MODERATING EFFECT OF DEMOGRAPHIC FACTORS OF BOARD OF DIRECTORS ON THE ASSOCIATION BETWEEN CORPORATE GOVERNANCE AND EARNINGS MANAGEMENT - Sakina Nusarifa Tantri; Mahfud Sholihin (Faculty of Economics and Business, Universitas Gadjah Mada, 2012)
This study aims to investigate whether corporate governance affects earnings management and if so whether such effect is moderated by age, gender, and educationalbackground of board of directors. Using Moderated Regression Analysis, this study examines a sample of 55 companies listed in the Indonesia Stock Exchange for the period of 2005 to 2009. The results show that corporate governance negatively affects earnings management. Further analyses reveal that the association is moderated by age, gender, and educational background of board of directors. Keywords: corporate governance, earnings management, age, educational background, gender.